Analisis Ketersediaan Koleksi Bahan Pustaka Terkait Pemenuhan Kebutuhan Informasi Pemustaka di TBM PMI Medan Denai - Yusniah Yusniah; Aina Sabriyanti; Mifta Huljannah Sihombing; Siti Pardiani Tanjung; Khoirunnisaa Khoirunnisaa5 (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The problem at the PMI Medan Denai Reading Park is that the collections are inadequate and the equipment is still limited, as can be seen from some visitors who are confused about finding the collections they need. In achieving the goal of a reading garden, what must be done by the manager is the procurement of collections for convenience and comfort in finding the information needed by users. This study uses a type of qualitative research, with a descriptive research approach. Descriptive research is research that seeks to describe current problem solving based on data. This type of qualitative descriptive research used in this study is intended to obtain information about the role of single parents in shaping the ethics of communication in children. This study resulted that the availability of library collections has not been able to meet the information needs of visitors at TBM PMI Medan Denai. Keywords: Role, Collection of Library Materials, Fulfillment of Information Need